2018
DOI: 10.1186/s12913-018-3080-3
|View full text |Cite
|
Sign up to set email alerts
|

Health economic evaluations based on routine data in Germany: a systematic review

Abstract: BackgroundImproved data access and funding for health services research have promoted the application of routine data to measure costs and effects of interventions within the German health care system. Following the trend towards real world evidence, this review aims to evaluate the status and quality of health economic evaluations based on routine data in Germany.MethodsTo identify relevant economic evaluations, a systematic literature search in the databases PubMed and EMBASE was complemented by a manual sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
2
19
0
2
Order By: Relevance
“…Gansen [111] found that the principal illnesses assessed were cardiovascular diseases followed by type II diabetes mellitus whereas neoplasms were the main focus of evaluation in our review. This may be due to the fact that Gansen [111] only reviewed studies performed in Germany.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Gansen [111] found that the principal illnesses assessed were cardiovascular diseases followed by type II diabetes mellitus whereas neoplasms were the main focus of evaluation in our review. This may be due to the fact that Gansen [111] only reviewed studies performed in Germany.…”
Section: Discussionmentioning
confidence: 92%
“…A systematic review of the use of RWD for EE in Germany was identified [111] and some comparisons with this are presented below. However, some inclusion criteria differ from those of the present study, such as studies that use routine data as a source of information for costs or effects or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it needs to be noted that a bottom-up approach could have potentially provided more accurate cost estimates than the top-down approach used in our analysis. However, claims data are a comprehensive and reliable basis that have become an important data source for health economic evaluations [41,42]. Furthermore, we only analyzed filled prescriptions in our database.…”
Section: Limitationsmentioning
confidence: 99%
“…In den nachfolgenden Sektor-spezifischen Artikeln sollen deshalb getrennte Vorgehensweisen zu primärdaten-, sekundärdaten-oder listenbasiertem Costing beschrieben werden. In diesem Zusammenhang ist auch eine Zunahme von Kostenberechnungen mit Hilfe von GKV-Routinedaten zu beobachten, die zumindest bei einer GKV-Perspektive die Probleme der oben genannten Studiendesigns teilweise lösen können, obschon sie auch eigene Unsicherheiten mit sich bringen [15], [16]. Der Besonderheit dieser Art der Kostenberechnung soll in einem gesonderten (sechsten) Artikel Rechnung getragen werden.…”
Section: Studienartenunclassified